DEVELOPING SPEAKING FLUENCY THROUGH INTERACTIVE ACTIVITIES: AN EMPIRICAL STUDY IN EFL CONTEXT - Khaydarova , Ozoda (Effective scientific journals, 2026)
Speaking fluency remains one of the most challenging competencies for learners in English as a Foreign Language (EFL) contexts. Traditional teacher-centered methodologies often limit opportunities for authentic oral production. This study investigates the impact of interactive classroom activities on the development of speaking fluency among university-level EFL learners. Drawing upon Communicative Language Teaching (CLT), Task-Based Language Teaching (TBLT), and sociocultural theory, the research employs a quasi-experimental design with control and experimental groups. Data were collected through pre- and post-speaking tests, fluency metrics (speech rate, pause frequency, mean length of utterance), and learner perception surveys. Statistical analysis (paired t-test and regression model) demonstrates significant improvement in fluency among students exposed to structured interactive activities (p < .05). The findings confirm that interactive pedagogical strategies enhance spontaneous speech production, reduce hesitation phenomena, and increase communicative confidence. The study contributes to contemporary ELT methodology by proposing a structured interactive fluency model applicable in higher education EFL classrooms.